2015
DOI: 10.1242/jcs.172429
|View full text |Cite
|
Sign up to set email alerts
|

A novel mitochondrial pool of Cyclin E, regulated by Drp1, is linked to cell density dependent cell proliferation

Abstract: The regulation and function of the crucial cell cycle regulator cyclin E (CycE) remains elusive. Unlike other cyclins, CycE can be uniquely controlled by mitochondrial energetics, the exact mechanism being unclear. Using mammalian cells (in vitro) and Drosophila (in vivo) model systems in parallel, we show that CycE can be directly regulated by mitochondria through its recruitment to the organelle. Active mitochondrial bioenergetics maintains a distinct mitochondrial pool of CycE (mtCycE) lacking a key phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 53 publications
3
48
1
Order By: Relevance
“…DRP1 also demonstrates strong interactions with another cell cycle protein, cyclin E. Although it is unclear how this interaction regulates normal cell cycle progression, it is evident that inhibition of DRP1 leads to increased levels of cyclin E throughout the cell cycle, and especially during the G2/M transition (Mitra et al, 2009; Parker et al, 2015; Qian et al, 2012). This cyclin E buildup causes replication stress in the form of premature entry into a prolonged S-phase, chromosomal instability, and subsequent aneuploidy.…”
Section: Mitochondrial Dynamics During the Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…DRP1 also demonstrates strong interactions with another cell cycle protein, cyclin E. Although it is unclear how this interaction regulates normal cell cycle progression, it is evident that inhibition of DRP1 leads to increased levels of cyclin E throughout the cell cycle, and especially during the G2/M transition (Mitra et al, 2009; Parker et al, 2015; Qian et al, 2012). This cyclin E buildup causes replication stress in the form of premature entry into a prolonged S-phase, chromosomal instability, and subsequent aneuploidy.…”
Section: Mitochondrial Dynamics During the Cell Cyclementioning
confidence: 99%
“…This cyclin E buildup causes replication stress in the form of premature entry into a prolonged S-phase, chromosomal instability, and subsequent aneuploidy. Some stem cells demonstrate a similar profile of enhanced cyclin E, short G1, and long S-phase, and indeed, progenitor cell markers are upregulated in DRP1-inhibited cells (Parker et al, 2015). Interestingly, concurrent knockdown of the mitochondrial fusion protein, OPA1, with DRP1 abrogates the elevation of cyclin E levels (Qian et al, 2012), suggesting it may be the hyperfused mitochondrial morphology of DRP1-inhibited cells that causes increased cyclin E levels.…”
Section: Mitochondrial Dynamics During the Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…e dynamism of mitochondria is the result of two opposing processes: fusion, which leads to their merging into larger mitochondrial networks and ssion, which is the process of separation of an individual mitochondrion from the network. e morphology of mitochondria depends on the balance between these processes [3,[6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that mitochondrial fusion may be instructive for entry into S phase by, at least in part, promoting the buildup of the S phase-promoting protein Cyclin E (Mitra et al, 2009). It is currently unclear how this occurs, but a recent report suggests that a pool of Cyclin E protein is directly recruited to mitochondria (Parker et al, 2015). While these observations and others imply a direct mechanistic link between the cell cycle machinery and mitochondrial fission-fusion proteins (Horn et al, 2011; Mitra et al, 2009; Qiao et al, 2010; Taguchi et al, 2007), there is still much to understand regarding precise cellular and molecular interplay controlling proliferation.…”
Section: Introductionmentioning
confidence: 99%